Pyroptosis in the Initiation and Progression of Atherosclerosis - Qian, Zhengtao; Zhao, Yilin; Wan, Chuandan; Deng, Yimai; Zhuang, Yaoyao; Xu, Yeqiong; Zhu, Yanping; Lu, Shourong; Bao, Zhengyang (Frontiers in Pharmacology, 2021)
Pyroptosis, a newly discovered form of programmed cell death, is characterized by cell swelling, the protrusion of large bubbles from the plasma membrane and cell lysis. This death pathway is triggered by human and mouse caspase-1, human caspase-4 and caspase-5, or mouse caspase-11 and leads to gasdermin D (GSDMD)-mediated membrane pore formation and thus the release of cell contents and proinflammatory cytokines such as IL-1β and IL-18. Pyroptosis was initially found to function as an innate immune effector mechanism to facilitate host defence against pathogenic microorganisms, and subsequent studies revealed that pyroptosis also plays a vital role in inflammatory immune diseases and tumours. Recent studies have shown that pyroptosis is involved in the initiation, the progression and complications of atherosclerosis (AS). Here, we provide an overview of the role of pyroptosis in AS by focusing on three important participating cells: endothelial cells (ECs), macrophages, and smooth muscle cells (SMCs). In addition, we also summarized drugs and stimuli that regulate the progression of atherosclerosis by influencing cell pyroptosis.